Fostering Companies Planes to Avoid Disruption to their Supply Chain for Next Year - Sulaiman Sajilan; Gholamreza Zandi; Nira Hariyatie Hartani; Munwar Hussain Pahi (International Journal of Supply Chain Management, 2018)
The purpose of this study is to determine the role of leveraging multiple transportation modes to improve the avoidance of disruption in supply chain, to regulate the role of using back-up carriers to improve the avoidance of disruption in supply chain, to regulate the role of utilizing Utilize Strategic Partner Carriers to improve the avoidance of disruption in supply chain and to regulate the role of shift freight to alternate ports to improve the avoidance of disruption in supply chain. Sample size was of 40. Population has been taken from the management dealing supply chain sector. In cross sectional study, 5-point Likert scale questionnaire has been used to obtain the response. Four factors have been played the role to improve the avoidance of disruption in supply chain sector. The leveraging of multiple transportation modes, use back-up carriers, utilize strategic partner carriers and shift freight to alternate ports. All these elements low the risk of disruption in supply chain management.